Observation of the local electromechanical response in 2-2 ceramic-ceramic lead-free ferroelectric composites via digital image correlation - Martin, Alexander; Maier, Juliana; Kakimoto, Ken-ichi; Kamlah, Marc; Webber, Kyle Grant (Journal of Applied Physics, 2024)
This study investigates bilayers of 0.94(Na1/2Bi1/2)TiO3-0.06BaTiO3 (NBT-6BT) and 0.90(Na1/2Bi1/2)TiO3-0.06BaTiO3-0.04(K0.5Na0.5)NbO3 (NBT-6BT-4KNN) using digital image correlation, enabling the separate analysis of strain response in each layer. The bilayers were electrically connected without mechanical connection (polarization coupled) as well as mechanically and electrically connected (polarization and strain coupled) to determine the role of interlayer mechanical interactions. The large signal longitudinal and transverse piezoelectric coefficients, d 33 ∗ and d 31 ∗ , were characterized for both cases. In the polarization coupled composite, d 33 ∗ decreased linearly from 410 to 260 pm/V with increasing vol. % NBT-6BT. In contrast, in the polarization and strain coupled case, d 33 ∗ and d 31 ∗ were maximum at 50 vol. % NBT-6BT with values of 440 and −130 pm/V, respectively, highlighting the critical role of strain interactions in ceramic-ceramic composites. The stress-induced phase transformation through strain coupling significantly impacted the electromechanical response, with improved strain values observed in the NBT-6BT-4KNN layer. Furthermore, this study highlights the variability in the significance of strain coupling within bilayer systems as a function of the altering volume fraction of their constituent components.
CRIS-Team Scopus Importer:2024-02-16